2007
DOI: 10.1080/09540120701207833
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access to medical cannabis for Canadians living with HIV/AIDS

Abstract: North American studies suggest that as many as one-third of people living with HIV/AIDS self-medicate with cannabis for relief of physical and stress-related symptoms. Although cannabis remains a controlled substance in Canada, legal access has been granted to people with HIV/AIDS and other serious illness under the Marihuana Medical Access Regulations (MMAR) since 2001. Several years into the programme, however, few Canadians ( approximately 1400) have obtained MMAR approval, suggesting that substantial obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 10 publications
3
34
1
Order By: Relevance
“…Previous studies of medical users all found that smoking was the most commonly used and most preferred mode, in contrast to the current study’s findings [79, 2730]. Among past studies that examined vapourizer use, the prevalence of using a vapourizer was generally low, falling between 8 and 20 % [7, 28, 29]. However, one Canadian study, conducted in 2007, found that 88 % of approved medical users smoked, 72 % ate it, and 52 % used a vapourizer, which offers similar estimates to the current study [27].…”
Section: Discussioncontrasting
confidence: 98%
“…Previous studies of medical users all found that smoking was the most commonly used and most preferred mode, in contrast to the current study’s findings [79, 2730]. Among past studies that examined vapourizer use, the prevalence of using a vapourizer was generally low, falling between 8 and 20 % [7, 28, 29]. However, one Canadian study, conducted in 2007, found that 88 % of approved medical users smoked, 72 % ate it, and 52 % used a vapourizer, which offers similar estimates to the current study [27].…”
Section: Discussioncontrasting
confidence: 98%
“…Despite growing legal access to cannabis for PLWHA in Canada/North America and growing evidence of its effectiveness for symptom management in HIV care (Abrams et al, 2003; Abrams et al, 2007; Department of Justice Canada, 2011; Ellis et al, 2009; Haney et al, 2007) many healthcare practitioners remain reluctant to prescribe cannabis to patients (Belle-Isle & Hathaway, 2007). In order to support decisions to prescribe cannabis and cannabinoids, physicians will require additional evidence regarding the long-term impact of cannabis use on the health of cannabis users.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, although cannabis remains a controlled substance in Canada, in recent years the courts have upheld the right to use for serious medical conditions without fear of criminal sanction (Hathaway, 2001). It was in response to one such ruling (Belle-Isle & Hathaway, 2007) that Health Canada introduced the Marihuana Medical Access Regulations to meet this constitutional requirement.…”
Section: Social Capital Community and Healthmentioning
confidence: 97%